De profetas y eremitas: luces y sombras (2020)
The mystical experience has been present at all times and has been anchored to religions, which have taken moments of ecstasy from different people to deepen their dogmatic or strengthen their believers. In spite of the negative that can be said about this matter, we have to notice the clearly differentiated aspects at the moment of speaking of the ecstasy in which this experience or experience fall: on the one hand we have the prophecy, on the other, the eremiritarismi. In the first, feeling predominates, in the second knowledge does. The prophet and the hermit must arrive at the same place: an experience that links them to their God or their Deity. Beyond what can be done according to each religious institution, we must note that both routes have elements in common and clearly denoted differences. Here is the objective or our article: to show the lights and shadows that may exist in the face of two types of divine experiences that, despite having a common horizon, are radically opposed. Our approach is limited to what is termed as phenomenology of religion.